Dismissal during the Trial Period and the Fundamental Rights of the Worker - De La Cruz, Jaime Gerónimo (2024)
This investigation arises from the need to provide real protection to thousands of workers who are unjustifiably dismissed during the trial period, whose right to work would be violated. The justification and importance of the study of the institution of the probationary period is due to the legislative disinterest in the fundamental rights of a vulnerable sector in the workplace, the workers. In this line of ideas, the aforementioned article analyzes doctrinally and jurisprudentially the figure of the probationary period with the objective of identifying the true nature and foundation of this institute, which will help determine under what assumptions dismissals during the probationary period are constituted as arbitrary. The investigation determines that, as a general rule, dismissals granted during the trial period are at the discretion of the employer; however, such dismissals must be subject to law, otherwise they will be arbitrary.